Prevalence of sexually transmitted infections (STIs), associations with sociodemographic and behavioural factors, and assessment of the syndromic management of vaginal discharge in women with urogenital complaints in Mozambique - Manjate, Alice; Sergon, Gladys; Kenga, Darlenne; Golparian, Daniel; Tyulenev, Yuriy; Loquilha, Osvaldo; Mausse, Fabião; Guschin, Alexander; Langa, José Carlos; Passanduca, Alfeu; Sacarlal, Jahit; Unemo, Magnus (Frontiers in Reproductive Health, 2024)
In Mozambique, sexually transmitted infections (STIs) are estimated to be prevalent, but diagnosis and treatment of curable STIs rely only on syndromic management. We examined the prevalence of four non-viral STIs and HIV-1/2, based on etiological diagnosis, associations with sociodemographic and behavioural factors, and the STI diagnostic accuracy of the vaginal discharge syndromic management in women with urogenital complaints in Maputo, Mozambique. A cross-sectional study was performed in Maputo, Mozambique, February 2018–January 2019, enrolling 924 women of reproductive age with urogenital complaints. Endocervical/vaginal swabs were sampled and chlamydia, gonorrhoea, trichomoniasis and Mycoplasma genitalium infections were diagnosed using a multiplex real-time PCR (AmpliSens; InterLabServices). Serological testing was performed for HIV-1/2. A structured questionnaire collected metadata. All data were analyzed in STATA/IC 12.1 using descriptive statistics, chi-square tests and logistic regression model. About 40% of the women were less than 24 years old, 50.8% were single, 62.1% had their sexual debut between 12 and 17 years of age, and the main complaint was vaginal discharge syndrome (85%). The prevalence of chlamydia was 15.5%, trichomoniasis 12.1%, gonorrhoea 4.0%, M. genitalium 2.1%, and HIV-1/2 22.3%. The vaginal discharge syndrome flowchart had a sensitivity of 73.0%–82.5% and a specificity of 14%–15% for the detection of any individual non-viral STI in women with urogenital complaints. In total, 19.2% of the symptomatic women with chlamydia, trichomoniasis or gonorrhoea would not be detected and accordingly treated using the vaginal discharge syndromic management (missed treatment) and 70.0% of the women would be treated despite not being infected with any of these three STIs (overtreatment). In conclusion, a high prevalence of especially chlamydia, trichomoniasis, and HIV-1/2 was found in women of childbearing age with urogenital complaints in Maputo, Mozambique. Syndromic management of vaginal discharge revealed low accuracy in the detection of STIs in symptomatic women, especially low specificity, which resulted in under-treatment of STI-positive cases and incorrect or over-treatment of women with urogenital complaints, many of whom were negative for all the non-viral STIs. Etiological diagnosis is imperative for effective management of STIs in symptomatic and asymptomatic women.